KONJENİTAL DİYAFRAGMA HERNİSİ (19781998) - CELAYİR, Sinan; İLÇE, Zekeriya; KILIÇ, Nizamettin; SARIMURAT, Nüvit; ERDOĞAN, Ergun; YEKER, Daver (Cerrahpaşa Medical Journal, 2019)
Background and Design.-This study was carried out to determine and discuss the current status of Congenital Diaphragmatic Hernia (CDH). For this reason 74 newborns with CDH, which were treated in our unit between 19781998 were reviewed retrospectively. The cases have been divided into two groups as Group I which corresponds to cases admitted before 1992 and group II which corresponds to cases admitted after 1992. Age at admission; type of defect and surgical techniques in relation with mortality and complication rate were compared between these groups. CDH was diagnosed using prenatal ultrasound, postnatal clinical evaluation and xray studies. In addition, all cases in Group II have been controlled with blood gas samples. Results.-While in group I surgery was performed on an emergency basis within first 6 hours after admission, this time extended to 16 hours for Group II cases until stabilization had been achieved. 61 of 74 patients could be operated (Group I: 50, Group II: 11). Primary closure was the surgical procedure of choice regardless of the size of the defect. In the series, associated anomaly incidence was 36.2%, complication rate was 33.8% and mortality rate was 35.1%. Conclusion.-Although there was a statistical difference in regard to complication rate between the groups, there was no significant difference between the mortality and type of diaphragmatic defect. Additionally there was no statistical significance between the preferred surgical technique, the type of defect and the mortality.